Impact of Authentic Inquiry on Undergraduate Students' Self-Reported Understanding of Scientific Practices. (26th September 2022) - Macik, Maria; Ben Wu, X.; Sandoval, Carolyn
Abstract : Science literacy, and specifically the understanding of scientific practices, has been identified as an important outcome for college students. Educational researchers have investigated various instructional strategies in search of effective methods for fostering students' understanding of scientific practices. One such instructional practice that can be implemented in large-enrollment science courses is authentic inquiry. To explore the effects of authentic inquiry projects on students' learning of scientific practices, we analyzed qualitative data from a student survey over several semesters of an introductory ecology course. The qualitative data gave insight into the mechanisms which influenced students' learning and skill acquisition. Qualitative results support the finding that the authentic inquiry project contributed to students' learning of scientific practices, and students identified several aspects of the inquiry project that contributed to their interest and learning. Findings of this study contribute to filling the research gap on the relationship between scientific practices and students learning and can be useful for instructors seeking practical strategies for implementing authentic inquiry into their large-enrollment science courses.